2018
DOI: 10.1161/hypertensionaha.118.11770
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, Anxiety, and Blood-Brain Barrier Permeability Are Increased in Postpartum Severe Preeclampsia/Hemolysis, Elevated Liver Enzymes, and Low Platelet Count Syndrome Rats

Abstract: Hypertension and inflammation during pregnancy are suggested to contribute to the development of post-partum depression and anxiety. Using a rat model of severe preeclampsia and Hemolysis Elevated Liver enzymes Low Platelet syndrome which displays both hypertension and inflammation during pregnancy we evaluated whether rats were prone to develop depression or anxiety in the post-partum period. On gestational day 12, mini-osmotic pumps infusing sFlt-1 and sEng were placed into rats, a subset of these rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…Increased circulating sFlt1 in preeclampsia is implicated in development of vasculopathy that underline proteinuria, disruption of the BBB and cerebral edema (Miller., 2019). Moreover, sFlt1 infusion to pregnant rats induces preeclampsia-like syndrome (Wallace et al, 2018). The results of the present work showed increased sFlt1 and TNF-α in the PE group compared to control pregnant group.…”
Section: Discussionsupporting
confidence: 52%
“…Increased circulating sFlt1 in preeclampsia is implicated in development of vasculopathy that underline proteinuria, disruption of the BBB and cerebral edema (Miller., 2019). Moreover, sFlt1 infusion to pregnant rats induces preeclampsia-like syndrome (Wallace et al, 2018). The results of the present work showed increased sFlt1 and TNF-α in the PE group compared to control pregnant group.…”
Section: Discussionsupporting
confidence: 52%
“…49 Pregnant rats infused with sFlt-1 and sEng developed a PE-like syndrome and increased BBB permeability in the postpartum period. 50 Exposing rat cerebral vessels to serum from women with PE resulted in an 18-fold increase in BBB permeability; surprisingly, this effect was prevented by VEGF inhibition. 44 Placental-ischemic rats had evidence of cerebral edema and neuroinflammation 2 months postpartum, suggesting that the deleterious effects of PE on the NVU persist after delivery.…”
Section: Preeclampsia and The Cerebral Vasculature: Insights From Basmentioning
confidence: 99%
“…Hecht et al [14] recently identified from 317 autopsies of women who died of eclampsia not only "brain perivascular edema" (68.4%), which was unsurprising, but also liver lesions characterized by "periportal hemorrhage and dilation of the sinusoids" (72.2% in this series) as the predominant problems. The presence of HELLP syndrome is also characterized by impaired capillary perfusion [15] and increased permeability to plasma proteins, and it may be linked to cerebral edema [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%